Strategies To Enhance Customer Satisfaction With The Quality Of Beef Meatball Products At Bakso Robin Panjer - Zebua, Kezia Evangelista; Dewa Ayu Anom Yuarini; I Wayan Gede Sedana Yoga (Cita konsultindo, 2026)
This study analyzes a significant sales decline of 20–30% for beef bakso at Bakso Robin Panjer, a direct consequence of intense market competition. The primary objective is to formulate an effective product quality improvement strategy utilizing the Quality Function Deployment (QFD) methodology. QFD, a framework applicable to address sales decline, was instrumental in identifying the critical quality attributes for subsequent evaluation and enhancement to ensure consumer satisfaction. This research identified 10 attributes influencing consumer satisfaction, namely: color, appearance, size, portion, shape, temperature, texture, aroma, taste, and doneness level. Based on a survey of 97 consumers, while all 10 quality attributes were rated as highly important, the satisfaction analysis uncovered a significant performance gap. Specifically, the sensory attributes of aroma (satisfaction score 3.79; improvement ratio 1.32), taste (3.86; improvement ratio 1.30), and texture (4.21; improvement ratio 1.19) were identified as the highest priorities for intervention due to their comparatively low satisfaction ratings. The subsequent House of Quality (HoQ) matrix analysis concluded that the technical strategy must be concentrated on four critically important process parameters: boiling (relative importance 22.4%), dough mixing (20.2%), meatball forming (16%), and raw material procurement (11.5%). The resulting strategic recommendations include dough reformulation by increasing the meat-to-filler ratio and incorporating aromatic spices, standardization of the boiling temperature to ensure consistent broth quality and doneness, and the utilization of a forming machine to guarantee product shape and texture consistency. These targeted interventions are projected to restore the company's competitiveness and maximize overall consumer satisfaction.